Pediatric airway reconstruction with a prefabricated auricular cartilage and radial forearm free flap. (30th January 2015) - Ahmad, Faisal I.; O'Dell, Karla; Peck, Jessica J.; Wax, Mark K.; Milczuk, Henry A.
<x xml:space="preserve">Abstract</x> Prefabricated composite free flaps for complex airway reconstruction have been described for an adult series at our institution. We extended this approach to a pediatric patient with lifelong subglottic stenosis who had failed previous open airway reconstructions. A staged procedure was utilized in which a composite graft was created using conchal cartilages and a radial forearm free flap. This reconstruction improved the patency of her airway and decreased her dependency on intermittent airway dilations. Airway reconstruction with prefabricated conchal cartilage composite free flaps may be used as a salvage procedure for complex pediatric airway reconstruction when other methods have failed. Laryngoscope, 125:1979–1982, 2015